2016
DOI: 10.1039/c6cp00561f
|View full text |Cite
|
Sign up to set email alerts
|

K- and L-edge X-ray absorption spectrum calculations of closed-shell carbon, silicon, germanium, and sulfur compounds using damped four-component density functional response theory

Abstract: X-ray absorption spectra of carbon, silicon, germanium, and sulfur compounds have been investigated by means of damped four-component density functional response theory. It is demonstrated that a reliable description of relativistic effects is obtained at both K- and L-edges. Notably, an excellent agreement with experimental results is obtained for L2,3-spectra-with spin-orbit effects well accounted for-also in cases when the experimental intensity ratio deviates from the statistical one of 2 : 1. The theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 94 publications
0
50
0
Order By: Relevance
“…83 Recently a damped response study showed that this branching ratio in L-edge XANES was reproduced well from four-component full relativistic density function theory. 84 Similarly, SOC should also play an important role in L-edge XCD. However, the sizes of the molecules in this study and the numbers of the involved excited states prohibit a full relativistic calculation.…”
Section: Computational Approachmentioning
confidence: 99%
“…83 Recently a damped response study showed that this branching ratio in L-edge XANES was reproduced well from four-component full relativistic density function theory. 84 Similarly, SOC should also play an important role in L-edge XCD. However, the sizes of the molecules in this study and the numbers of the involved excited states prohibit a full relativistic calculation.…”
Section: Computational Approachmentioning
confidence: 99%
“…The computational cost is similar to the eigenvalue response equation and DFT kernels are required also in this case. In the context of relativistic theories with variational SO interaction, the methodology has been developed in the spin-orbit ZORA 42 , and 4c 43,44 framework and applied to the calculation of frequency-dependent dipole polarizabilities 45 , electronic absorption spectra in valence and X-ray regions 46,47 , and electric dipole dispersion interaction coefficients 48 . An extensive list of review texts on eigenvalue and damped response theory can be found in Table 1 in Ref.…”
Section: Please Cite This Article As Doi:101063/15128564mentioning
confidence: 99%
“…The effects of correlation and relativity are not additive, and non-perturbative theories are ideally suited for handling them together. We should also mention that this is not only true for core IP processes but also for more complex processes 9,[88][89][90][91][92][93] leading all the way to multi-reference theories with relativistic Hamiltonians which are being actively investigated. [94][95][96][97][98][99][100][101] We have also assessed the lowest order Quantum Electrodynamic (QED) correction to the core IP.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recently, advances in electron correlation theories have made the accurate prediction of Xray ionization and excitation spectra viable. [6][7][8][9] A high level correlation theory should, in principle, take care of correlation and orbital relaxation in a generic situation involving energy differences of the ground and ionized, electron attached, or excited states. However, for core IP in particular, a proper correlation theory must also accurately capture not only a partial cancellation of dynamic correlation between the states but also take account of the large orbital relaxation in an explicit manner.…”
Section: Introductionmentioning
confidence: 99%